2012
DOI: 10.2136/sssaj2011.0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage and Residue Management on Soil Organic Carbon and Total Nitrogen in the North China Plain

Abstract: A suitable tillage‐residue management system is needed in the North China Plain (NCP) that sustains soil fertility and agronomic productivity. The objectives of this study were to determine the effects of different tillage‐residue managements for a winter wheat (Triticum aestivum L.) and summer maize (Zea mays L.) double‐crop system on soil organic carbon (SOC) and total N pools. No‐tillage with residue cover (NTR), no‐tillage with residue removed and manure applied (NTRRM), and conventional tillage with resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 50 publications
2
27
0
2
Order By: Relevance
“…In the present studied field, Hou et al. () observed that wheat yield tended to be lower under NT than CT from 2004 to 2009. Based on the analysis of wheat yield components, Kumudini et al.…”
Section: Introductionmentioning
confidence: 49%
“…In the present studied field, Hou et al. () observed that wheat yield tended to be lower under NT than CT from 2004 to 2009. Based on the analysis of wheat yield components, Kumudini et al.…”
Section: Introductionmentioning
confidence: 49%
“…No-till (No-Till) farming sequesters more C close to the soil surface than does conventionally tilled (Till) farming, whereas Till stores more C deeper in the profile (Baker et al, 2007;Hou et al, 2012). However, the fate of this surface-sequestered C in No-Till soil is unclear under warming and post-warming conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable interest has recently been generated by the assessment of spatial distributions and variations in SOC concentrations and stocks in various ecosys-tems at site, local, slope, watershed, regional, continental, and global scales (Burnham and Sletten, 2010;Han et al, 2010;Hou et al, 2012;Huo et al, 2013;Jimenez et al, 2008;Lal, 2004b;Liu et al, 2011;Tornquist et al, 2009;Van Minnen et al, 2009;Wang et al, 2003Wang et al, , 2010a. These studies have enriched the understanding of the patterns and control of SOC distributions at these scales.…”
mentioning
confidence: 99%